Uji Aktivitas Antioksidan Teh Herbal Biji Durian (Durio zibethinus Murr.) dengan Tambahan Daun stevia (Stevia rebaudiana Bertoni) sebagai Pemanis Alami dengan Metode DPPH - Andry, Muhammad; Ramadaini, Tiara; Marseli, Cindy; Nurfitriyana, Nurfitriyana; Azzahra, Rafifah; Syahputra, Hafid; Shiyan, Shaum (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Free radicals are an important health concern due to their role in the development of various diseases. Antioxidants, capable of neutralizing free radicals, are abundant in plants such as durian seeds (Durio zibethinus Murr.) and stevia leaves (Stevia rebaudiana Bertoni). Herbal tea formulated from these materials has potential as an alternative functional drink because both contain phenolic compounds with antioxidant activity. This study aimed to evaluate the potential of durian seeds and stevia leaves as herbal tea with antioxidant properties. The research involved sample collection, identification, preparation of simplicia, characterization, formulation of herbal tea, quality testing, and determination of antioxidant activity. The simplicia characteristics of durian seeds and stevia leaves showed water content of 6.16% each, water-soluble extract of 35% and 15.8%, ethanol-soluble extract of 25.5% and 14.6%, total ash of 0.73% and 0.3%, and acid-insoluble ash of 0.5% and 0.26%. Quality testing of the herbal tea showed water content of 2.18%, total ash of 3.90%, water-soluble ash of 73.85%, and acid-insoluble ash of 3.80%. Antioxidant activity based on IC50 values was 68.45 ± 1.32 ppm for durian seed tea, 61.6 ± 1.05 ppm for stevia tea, 39.28 ± 0.98 ppm (1:1), 44.64 ± 1.11 ppm (1:2), and 42.32 ppm ± 1.07 (2:1). These results indicate that combining durian seeds and stevia leaves can enhance antioxidant activity compared to individual extracts. Overall, durian seeds and stevia leaves can be developed into herbal tea formulations with very strong antioxidant activity, as reflected in their ability to reduce DPPH radicals. Radikal